2016
DOI: 10.1590/0034-737x201663060016
|View full text |Cite
|
Sign up to set email alerts
|

Substratos e ácido indol-3-butírico na produção de mudas de pitaia vermelha de polpa branca

Abstract: RESUMO A pitaia é uma cactácea frutífera originária das florestas tropicais da América do Sul e Central. Produz frutos não convencionais muito apreciados, com grande potencial para diversificação do setor. É propagada preferencialmente por estaquia, proporcionando aumento na precocidade e uniformidade dos pomares. Com o intuito de maximizar a produção de mudas, objetivou-se avaliar diferentes concentrações de ácido indol-3-butírico (AIB) e de três tipos de substratos na produção de mudas de pitaia (Hylocereus … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 19 publications
0
6
0
2
Order By: Relevance
“…Silva et al (2006) reported that different substrates had different effects on the root fresh matter of purple pitaya. Galvão et al (2016) observed that the use of sand, soil, or a combination of both had significant effects on the root fresh and dry matter of white-fleshed red pitaya (H. undatus). In the current study, the type of the substrate also significantly influenced shoot dry matter, budding volume, and number of areoles (Table 5).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Silva et al (2006) reported that different substrates had different effects on the root fresh matter of purple pitaya. Galvão et al (2016) observed that the use of sand, soil, or a combination of both had significant effects on the root fresh and dry matter of white-fleshed red pitaya (H. undatus). In the current study, the type of the substrate also significantly influenced shoot dry matter, budding volume, and number of areoles (Table 5).…”
Section: Resultsmentioning
confidence: 99%
“…Ceres, Viçosa, v. 68, n.4, p. 276-284, jul/aug, 2021 found that substrates containing higher levels of nutrients and organic matter improved all root parameters, except root fresh matter. Galvão et al (2016), when analyzing plant growth in different substrates, concluded that soil and a mixture of sand and soil led to higher shoot fresh matter, shoot dry matter, and root dry matter, whereas sand resulted in higher root fresh matter. In line with these data, Santos et al (2010a) reported that washed sand led to higher root fresh matter and that substrates containing composted cattle manure (rich in organic matter) produced plants with higher shoot fresh matter.…”
Section: Irrigation Frequencymentioning
confidence: 99%
See 1 more Smart Citation
“…The propagation of red pitaya is usually asexual via cuttings. Plants produced from this method result in an early yield and create uniform plantations in terms of their phenological characteristics and desirable fruit quality (ANDRADE et al, 2007;GALVÃO, 2015;. Lima (2013) and Marques et al (2011) found that Hylocereus undatus propagules produced from cuttings of 25 centimeters (cm) long rooted better than those of a shorter length.…”
Section: Introductionmentioning
confidence: 99%
“…De acordo Almeida et al (2016a), a aplicação de auxina exógena, na base de estacas, favorece a iniciação de raízes adventícias de H. undatus. Segundo Galvão (2015), o AIB é um dos fitoreguladores mais usados para estimular o enraizamento de estacas, pois é compatível com a maioria das espécies, mesmo em altas doses. Lone et al (2010) complementaram que o ácido indolbutírico (AIB) é pouco afetado por enzimas de degradação de auxinas, proporciona maior rapidez na produção de mudas e possibilita maior uniformidade de enraizamento.…”
Section: Introductionunclassified